On the evaluation of the U(3) content of the matrix elements of one- and two-body operators - Vanagas, V.; Castilho Aicarás, J. A. [UNESP] (AIP Publishing, 1992)
An expression for the U(3) content of the matrix elements of one- and two-body operators in Elliott's basis is obtained. Three alternative ways of evaluating this content with increasing performance in computing time are presented. All of them allow an exact representation of that content in terms of integers, avoiding Founding errors in the computer codes. The role of dual bases in dealing with nonorthogonal bases is also clarified. © 1992 American Institute of Physics.